Analisis Kebijakan Pemerintah Indonesia terhadap Ketimpangan Gender di Dunia Kerja - Nasiah, Zahrin; Hakim, Muhammad Lukman (Journal of Politics and Democracy, 2025)
Gender inequality in the Indonesian workplace is a critical and persistent issue despite the existence of various policy frameworks designed to address it. This study aims to critically analyze the effectiveness of Indonesian government policies in reducing gender inequality in the workplace and to identify the key factors contributing to the gap between regulation on paper and implementation on the ground. Using a qualitative approach with a literature study method, this research synthesizes and analyzes secondary data from government policy documents, laws and regulations, academic journals, and credible reports from national and international institutions. The findings reveal a significant paradox: on one hand, a robust and normative policy architecture is in place, yet on the other, empirical data indicates stagnant inequality, such as low female labor force participation rates (LFPR), a significant gender pay gap, and minimal representation of women in leadership positions. In-depth analysis concludes that this policy failure is caused by a combination of four main factors: (1) weak law enforcement and oversight, which renders policies symbolic; (2) 'gender-blind' policy design that ignores the reality of the double burden borne by women; (3) the hegemony of patriarchal socio-cultural norms that undermine the effectiveness of formal laws; and (4) policy fragmentation and weak synergy among government agencies. This research asserts that the problem lies not in the absence of laws, but in a systemic failure of implementation.